Applications of the high power laser in pediatric dentistry - Angeles Maslucan, Romy (2021)
The laser was integrated into the medical sciences in the 70s and is constantly evolving. In the dental market we find high power lasers, such as the Argon, Diode, Nd: YAG, Er, Cr: YSGG, Er: YAG and CO2 lasers. The most highlighting applications of the diode laser are in soft tissues and the Erbium laser are for hard tissues. Among the advantages of high-power lasers is to accelerate healing and the expression of collagens, disinfection of root canals in pulpectomies, and a decrease in dental permeability. In Pediatric dentistry, we must highlight the cavity preparation which generates the reduction in working time and an increase in patient collaboration due to the reduction/elimination of pain in procedures; such as avoiding the application of anesthesia. The points to be evaluated for the health professional is the cost/benefit and the necessary training to carry out the procedures with precision, accuracy and under all security measures.